The Evolution of Surgical Simulation: The Current State and Future Avenues for Plastic Surgery Education. Issue 2 (February 2017) - Kazan, Roy; Cyr, Shantale; Hemmerling, Thomas M.; Lin, Samuel J.; Gilardino, Mirko S.
Abstract : Summary: Alongside the ongoing evolution of surgical training toward a competency-based paradigm has come the need to reevaluate the role of surgical simulation in residency. Simulators offer the ability for trainees to acquire specific skills and for educators to objectively assess the progressive development of these skills. In this article, the authors discuss the historical evolution of surgical simulation, with a particular focus on its past and present role in plastic surgery education. The authors also discuss the future steps required to further advance plastic surgery simulation in an effort to continue to train highly competent plastic surgery graduates. Abstract : Video Discussion By Hooman Soltanian, M.D., is Available Online for this Article.